ANALISIS KEPUTUSAN KONSUMEN DALAM MEMILIH PAKAIAN BEKAS (CAKAR BONGKAR) DI PASAR SENTRAL KABUPATEN MIMIKA - Ananda Nursyazwani; Antje Tuasela (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to determine consumer interest in choosing used clothing (cakar bongkar) and socio-economic factors, work and environment influence consumer interest in choosing used clothing in the central market in Mimika Regency. The method used in this study is descriptive method and associative method. The data collected in this study are qualitative data and quantitative data sourced from consumers of used clothing (cakar bongkar) who are used as respondents using observation and questionnaire techniques. Data were analyzed using SEM PLS analysis. The results of the analysis show that, the work variable has a significant eflect on consumer buying interest. , while socio-economic and environmental factors do not have a significant eflect. Consumer interest in choosing used clothing (cakar bongkar) considers the work factor as a consideration, where this is based on the results of the analysis of the work factor has a significant eflect on consumer buying interest.